The Diuretic Effects of Coconut Water by Suppressing Aquaporin and Renin–Angiotensin–Aldosterone System in Saline-Loaded Rats - Wei, Jing; Zhao, Mantong; Meng, Keke; Xia, Guanghua; Pan, Yonggui; Li, Congfa; Zhang, Weimin (Frontiers in Nutrition, 2022)
The acute and prolonged diuretic effects of coconut water (CW) and the underlying mechanism were investigated with saline-loaded rat model. In acute diuretic experiment, CW could significantly increase urine excretion. In addition, the treatment of CW significantly increased urinary sodium ion, chloride ion, thereby considerably increasing the excretion of NaCl, however, the calcium concentration and pH value were hardly affected. In the prolonged diuretic experiment, CW dramatically increased the urine output and electrolyte concentrations (Na+, K+, Cl-). Furthermore, CW could suppress the activation of renin-angiotensin-aldosterone system by decreasing serum antidiuretic hormone, Ang II, and aldosterone levels, and significantly increasing serum atriopeptin level. CW treatment significantly down-regulate the mRNA expressions and protein levels of AQP1, 2, and 3. This report provided basic data for explaining the natural tropical beverage of CW as an alternative diuretic agent.